TMAO: a potential mediator of clopidogrel resistance - Ruisong Ma (Nature Portfolio, 2021)
Abstract Trimethylamine-N-oxide (TMAO) can activate platelets and increase thrombosis risk in clinical and experimental models. Meanwhile, the patients with coronary artery disease have higher serum TMAO level. However, it remains unknown whether Clopidogrel Resistance (CR) could be attributed to TMAO. The present study aimed investigate the effects of TMAO on clopidogrel in ischemia and reperfusion (IR) model in rats. Clopidogrel could (1) promote the production of platelets, induce an increase in the platelet-larger cell ratio; (2) prolong the tail bleeding time; (3) reduce platelet aggregation function, induced by ADP, and alleviate myocardial thrombus burden. TMAO could partially offset the effects of clopidogrel and induce CR. Thus, the present study demonstrated that circulating TMAO could reduce the inhibitory effects of clopidogrel on platelet aggregation. TMAO may be a potential mediator of clopidogrel resistance.